Importance Of Health Safety And Child Protection In K12 Schools - Sekhar, Basaboina Chandra (Digital Repository of Theses, 2025)
For providing students with a safe and secure learning environment, health and safety and child protection are essential elements. Safeguarding children's physical and emotional safety during their school days requires the implementation of several crucial procedures. Although child protection standards shield pupils from harm and neglect, health and safety procedures shield them from potential dangers like fire and infectious illnesses. Schools need to have procedures and regulations in place to avoid or tackle any threats concerning safety and well-being. This covers emergency preparation strategies, fire safety procedures, and infectious disease control. Therefore, the primary objective of this study is to analyse the importance of health safety and child protection in schools. Furthermore, more crucially, the study aims to examine the various causes and impacts of violence, bullying and harassment that students may experience in school on the children. It evaluates the significance of health and safety in schools and examines the significance of child protection in schools. The investigation employed a quantitative research approach to accomplish this goal. Students, parents and guardians, educators, school administrators, educators, education policymakers, and community people have all contributed to the study by providing responses. The outcome of the study suggested that most of the students felt at ease, although there are still issues with abuse and harassment that need to be resolved. Parents believe that the way schools handle behavioural and mental health issues is adequate. Teachers adhere to safety protocols and are encouraged by the organisation. While both parents and children express satisfaction with some aspects of the school's facilities, they also express concerns about upkeep and hygienic conditions. The appropriate training instructors receive on child safety and protection laws has a good effect on them. Overall, the study emphasises how important it is to prioritise child protection and school safety and makes recommendations for additional research and action. Keywords: Health and Wellbeing, Child Protection, Child Safety, Education Industry, Child Abuse, Child Harassment, prevention and policy Note: The data for the above research topic collected from well-established private schools only.